Performing in a Space Between Art and Life. (1st January 2018) - Abdulla, Bejhat Omer
Abstract : Artist Bejhat Omer Abdulla remembers his own story of fleeing Iraqi Kurdistan. Through this personal account, Abdulla demonstrates the challenges of crossing national, ethnic and ideological boundaries. This photographic essay begins by pointing to the complexity of the notion of who is a migrant as an abstract notion within academic and policy conversations about migration. Featuring original art work inspired by his first-hand experience as a migrant, Abdulla's account portrays one migrant's story in great detail, adding nuance and texture to what we know about the experiences of Kurdish migrants to Europe.